2021
DOI: 10.1096/fj.202100242r
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical overload‐induced muscle‐derived extracellular vesicles promote adipose tissue lipolysis

Abstract: How regular physical activity is able to improve health remains poorly understood.The release of factors from skeletal muscle following exercise has been proposed as a possible mechanism mediating such systemic benefits. We describe a mechanism wherein skeletal muscle, in response to a hypertrophic stimulus induced by mechanical overload (MOV), released extracellular vesicles (EVs) containing musclespecific miR-1 that were preferentially taken up by epidydimal white adipose tissue (eWAT). In eWAT, miR-1 promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 80 publications
3
49
0
Order By: Relevance
“…Conceptually, this would ensure that muscle consumes the appropriate amount of energy required for anabolism. Furthermore, this idea is in agreement with our previous work, where we show that EVs secreted by skeletal muscle during mechanical overload target adipose tissue, resulting in an increase in lipolysis [22]. This could be a mechanism whereby growing skeletal muscle signals to adipose tissue to increase the triacylglycerides that would support hypertrophic growth.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Conceptually, this would ensure that muscle consumes the appropriate amount of energy required for anabolism. Furthermore, this idea is in agreement with our previous work, where we show that EVs secreted by skeletal muscle during mechanical overload target adipose tissue, resulting in an increase in lipolysis [22]. This could be a mechanism whereby growing skeletal muscle signals to adipose tissue to increase the triacylglycerides that would support hypertrophic growth.…”
Section: Discussionsupporting
confidence: 92%
“…Previously, it was found that Cer plays a role in EV biogenesis by interacting with endosomes and lysosomes, initiating an ESCRTindependent pathway [32,75] via nSMase2, which is essential for exosome biogenesis in some cells [76]. We previously found that mice treated with an nSmase2 inhibitor (GW4869) had a significant decrease in EV concentration [22]. Cer is also important for mediating the EV response in the recipient cell, which suggests that this particular lipid adds to the functionality of EVs.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Currently several studies have investigated elements of the response of circulating small EVs to acute aerobic (Frühbeis et al, 2015;Guescini et al, 2015;Bertoldi et al, 2018;D'Souza et al, 2018;Lovett et al, 2018;Oliveira et al, 2018;Whitham et al, 2018;Brahmer et al, 2019;Yin et al, 2019;Karvinen et al, 2020;Rigamonti et al, 2020;Gao et al, 2021;Neuberger et al, 2021;Zhang et al, 2021), resistance (Annibalini et al, 2019;Just et al, 2020;Vechetti et al, 2021) or combined plyometric and downhill running (Lovett et al, 2018) exercise. Most of these studies have attempted to characterize circulating small EVs separated from plasma (Frühbeis et al, 2015;Guescini et al, 2015;D'Souza et al, 2018;Lovett et al, 2018;Whitham et al, 2018;Annibalini et al, 2019;Brahmer et al, 2019;Yin et al, 2019;Just et al, 2020;Rigamonti et al, 2020;Gao et al, 2021;Neuberger et al, 2021;Vechetti et al, 2021), although four studies have separated small EVs from serum (Bertoldi et al, 2018;Oliveira et al, 2018;Karvinen et al, 2020;Zhang et al, 2021).…”
Section: Changes In the Small Extracellular Vesicle Profile In Response To Acute Exercisementioning
confidence: 99%